DAMPAK TERPAAN IKLAN SHOPEE COD TERHADAP MINAT BELI PEREMPUAN - Agung Raharjo; Fajar Kurniawan; Fitriyanto; Faikoh Umairoh; Marulitua A, Bonardo (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2023)
The increasingly rapid advances in technology can be a determining factor in the success of an advertisement in reaching buyers' interest in a particular product. The development of e-commerce with a variety of shopping options makes consumers increasingly intent on buying instantly. Advertising exposure to consumer buying interest is high with several services that e-commerce provides in its sales. This research aims to evaluate whether exposure to the